INTEGRASI ILMU DAN AGAMA; STUDI ATAS PARADIGMA INTEGRASI, KOMPARASI, DIFUSI MENUJU PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI (PTKIN) YANG UNGGUL - Aris Muzhiat; Mulyadi Kartanegara (Al Qalam, 2020)
This research departs from the problem of scientific integration that never ends. In the midst of these problems, State Islamic University (UIN) of Sultan Maulana Hasanuddin (SMH) Banten as one of Islamic Higher Education Institutions has made the scientific paradigm of integration-comparative-diffusion as the development of the integration of religious and scientific sciences. This research will answer several problems, how is the integrative-comparative-diffusion paradigm as the scientific foundation of UIN SMH Banten, as well as its implementation in curriculum preparation. By using a qualitative approach and interactive analysis. This research resulted in two findings, including epistemologically the scientific paradigm of UIN SMH Banten about integration-comparative-diffusion which is a development of Islamic epistemology developed by Ismail Razi al-Faruqi and Kuntowijoyo who try to unite religion and science as a scientific model in religious education institutions. Islam. Second, the practical arrangement of the curriculum using the integration-comparative-diffusion scientific paradigm, is still very limited and still theoretical, because it has not been translated into the student curriculum. This concept does not describe the four domains of the curriculum, namely the philosophical, material, methodological, and strategic domains.